2017
DOI: 10.1016/j.resinv.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the distance covered in the incremental shuttle walk test and lung function and health status in patients with chronic obstructive pulmonary disease

Abstract: The ISWT is more independent of health status and pulmonary function in patients with mild COPD compared to moderate or severe cases. Therefore, the exercise capacity of patients with mild COPD should be estimated by the ISWT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In patients with moderate and severe COPD, the distance covered during the ISWT is significantly associated with pulmonary function parameters, such as vital capacity and airway obstruction (FEV 1 ), as well as health-related quality of life ( 35 ). According to Yildiz et al ( 36 ), the ISWT distance is significantly associated with FEV 1 ( r = 0.65) and FVC ( r = 0.54) in adults with bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with moderate and severe COPD, the distance covered during the ISWT is significantly associated with pulmonary function parameters, such as vital capacity and airway obstruction (FEV 1 ), as well as health-related quality of life ( 35 ). According to Yildiz et al ( 36 ), the ISWT distance is significantly associated with FEV 1 ( r = 0.65) and FVC ( r = 0.54) in adults with bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
“…The lung function findings observed in our study were similar to those observed by Li et al (17) in Chinese patients who presented a mean FVC and FEV 1 of 91%pred and 72%pred, respectively. In patients with moderate and severe COPD, the distance covered during the ISWT is significantly associated with pulmonary function parameters, such as vital capacity and airway obstruction (FEV 1 ), as well as health-related quality of life (35). According to Yildiz et al (36), the ISWT distance is significantly associated with FEV 1 (r = 0.65) and FVC (r = 0.54) in adults with bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 , 12 ] Consequently, the ISWT is considered to be a more standardized test than the 6MWD. [ 12 ] The ISWT is a test imposing an incremental acceleration as the patient walks round trips on a 10-meter course. [ 12 , 13 ] The test includes 12 levels, and each level lasts 1 minute.…”
Section: Methodsmentioning
confidence: 99%
“…[ 12 ] The ISWT is a test imposing an incremental acceleration as the patient walks round trips on a 10-meter course. [ 12 , 13 ] The test includes 12 levels, and each level lasts 1 minute. [ 12 , 13 ] The walking speed is determined by an audio signal and is increased every minute by 0.17 m/second from 0.50 m/second at the start to a final speed of 2.37 m/second at level 12.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation